New Interaction Solutions for a (2 + 1)-Dimensional Vakhnenko Equation - Qing Meng; Bin He (Complexity)
In this paper, we focus on the interaction solutions of a (2 + 1)-dimensional Vakhnenko equation. By using Hirota’s transformation combined with the three-wave method and with symbolic computation, some interaction solutions which include interaction solutions between exponential and trigonometric functions and interaction solutions between exponential and trigonometric and hyperbolic functions are presented.